PENERAPAN METODE GROUP INVESTIGATIONS DALAM PEMBELAJARAN MENULIS TEKS PROSEDUR PADA SISWA KELAS XI SMK - Adam Muklis Marwah; Dwi Agus; Wikanengsih Wikanengsih (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
In learning procedure text writing the majority of students get low grades, especially in developing their ideas into written material. In this study, the authors want to see the effectiveness of learning outcomes in the procedure of writing text skills by trying to apply the Group Investigations method to students to see how the writing results in writing procedure texts. This study aims to determine the differences in the learning outcomes of writing procedure texts with the application of the Group Investigations method to the learning of writing procedure texts of students in class XI Vocational High School. The research method used in this study is a descriptive qualitative method that describes the comparison of the results of student scores on learning to write procedure texts using the Group investigation method. The results show that there is an increase in the value of students after being given treatment. The average score at pretest was 72.5, the lowest score was 60, the average score was 75 and the highest score was 80, while the average score at posttest was 85, the lowest value was 80, the average score was 85, and the highest score was 95. This proved that the text learning process the procedure gets better. Students become richer in their vocabulary so that when given treatment students can clearly determine the general statement and structure of the procedure text. With the application of the Group Investigations method to Vocational High School students in class XI, they experience differences after being given treatment.